The religions book : big ideas simply explained /: big ideas simply explained. (2013) - Ambalu, Shulamit; Coogan, Michael David; Feinstein, Eve Levavi; (Rabbi), Freedman, Paul; Philip, Neil; Stobart, Andrew; Thompson, Mel, 1946-; Tieszen, Charles Lowell, 1978-; Weeks, Marcus
No abstract available